Crimes Against Children in Modern Criminological Perspective: A Case Study of Hafizah’s Murder in West Bangka - M. Adha Al Kodri; N Ghea Ardiella Achsa; M.Ikhzam Al Buchori; Isma Fadila; Isnanur Ananda (Jurnal Ragam Pengabdian, 2026)
This study examines crimes against children through a case study of Hafizah’s murder in West Bangka. The main research problem lies in the limited criminological explanation that connects child vulnerability, weak social supervision, criminal opportunity, and legal dilemmas when both the victim and the offender are children. This study aims to analyze the case from the perspective of modern criminology and to formulate community-based prevention strategies. This research applies a qualitative method with a case study design. Data were collected through unstructured interviews, field observations, and document analysis related to the case, child protection, and the juvenile criminal justice system. The findings show that Hafizah’s murder cannot be understood merely as an individual criminal act. The case emerged from the interaction between the victim’s vulnerability, weak social control, poorly supervised social spaces, and the absence of an effective early-warning mechanism within the community. The novelty of this study lies in its integration of routine activity theory, social control theory, and child victimology to examine a local child homicide case in a conceptual manner. This study contributes to modern criminological scholarship and offers a prevention model based on risk-area mapping, community guardianship, child safety education, and rapid reporting systems.